The role of epigenetic modifications in Alzheimer’s disease - ., Shierly; Wirawan, Chandra (International Journal of Research in Medical Sciences, 2020)
Aging is the primary risk factor for various neurodegenerative diseases, including Alzheimer’s disease (AD), which is the most frequent form of Dementia. AD is progressive neurodegenerative disease with abnormal protein production, inflammation and memory deterioration. The main clinical manifestations of this illness are cognitive disturbance and memory deficit. Abnormal of beta-amyloid (Aβ), neurofibrillary tangles (NFTs) and tau deposition are the most common findings pathology in this disease. Recent studies indicate that epigenetic modifications strongly correlate in developing these pathology and disease progression. The hallmarks of epigenetic modifications are DNA (deoxyribonucleic acid) methylation, histone modifications, chromatin remodeling and ncRNA (non-coding ribonucleic acid) expressions. This review aims to explain the potential mechanisms of epigenetic modifications associate with this disease. The general conclusion of this review is that epigenetic modifications play an ultimate role in AD and there are potential biomarkers of AD and future novel treatment of AD based on epigenetics.